2017
DOI: 10.1158/1541-7786.mcr-16-0327
|View full text |Cite
|
Sign up to set email alerts
|

miR-202 Diminishes TGFβ Receptors and Attenuates TGFβ1-Induced EMT in Pancreatic Cancer

Abstract: Previous studies in our laboratory identified that 3-deazaneplanocin A (DZNep), a carbocyclic adenosine analog and histone methyl transferase inhibitor, suppresses TGFβ-induced epithelial-to-mesenchymal (EMT) characteristics. In addition, DZNep epigenetically reprograms miRNAs (miRs) to regulate endogenous TGFβ1 levels via miR-663/4787 mediated RNA interference (Mol Cancer Res. 2016 Sep 13. pii: molcanres.0083.2016) (1). While DZNep also attenuates exogenous TGFβ-induced EMT response, the mechanism of this inh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…Moses et al reported that TGFβ binds to the heterodimeric type II and type I TGF‐β serine/threonine kinase receptors (TGFBR2 and TGFBR1) and initiates a signaling cascade through phosphorylation of SMAD2 and SMAD3 . TGFBR1 promoted cell proliferation, migration and invasion in lung cancer, pancreatic cancer, and glioblastoma . In this study, we reported that TGFBR1 promoted cell proliferation, migration, invasion and the cell cycle and inhibit cell apoptosis in HeLa and C33A cells.…”
Section: Discussionmentioning
confidence: 56%
“…Moses et al reported that TGFβ binds to the heterodimeric type II and type I TGF‐β serine/threonine kinase receptors (TGFBR2 and TGFBR1) and initiates a signaling cascade through phosphorylation of SMAD2 and SMAD3 . TGFBR1 promoted cell proliferation, migration and invasion in lung cancer, pancreatic cancer, and glioblastoma . In this study, we reported that TGFBR1 promoted cell proliferation, migration, invasion and the cell cycle and inhibit cell apoptosis in HeLa and C33A cells.…”
Section: Discussionmentioning
confidence: 56%
“…In human ESCCs, miR-202 regulated apoptosis by targeting HSF2 via mechanism involving caspase-3. A study also identified that miR-202 plays an important role in regulating cell proliferation, migration and invasion of cervical cancer (CC) by directly targeting cyclin D1, and miR-202 may represent a potential therapeutic target for patients with CC (16)(17)(18)(19)(20)(21)(22). In addition, a previous study showed that an increased serum concentration of miR-202 may be a strong independent prognostic factor for breast cancer patients (20).…”
Section: Discussionmentioning
confidence: 99%
“…As one of three TGF‐β receptors, TGFBR1 can regulate signal transduction rate through phosphorylating downstream Smad‐2 and Smad‐3 . Experimental studies have shown that TGFBR1 can promote malignant proliferation and metastasis of tumors by regulating epithelial‐mesenchymal transformation . Rosman et al and Zhou et al also revealed similar outcomes that TGFBR1*6A could promote the invasion and metastasis of MCF‑7 breast cancer cells and colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 89%